Особливості експресії TLR2 і TLR4 адипоцитами парапанкреатичної клітковини при експериментальному цукровому діабеті - Путілін, Денис Анатолійович; Камишний, Олександр Михайлович; Коновалова, О. О.; Камишна, Вiта Анатолiївна; Putilin, D. A .; Kamyshny, A . M.; Konovalova, О. О.; Kamyshnaya, V . А . (My University, 2014)
Досліджено вплив експериментального цукрового діабету на експресію TLR2 і TLR4 адипоцитами парапанкреатичної клітковини у щурів лінії Вістар. Встановлено, що розвиток ЕЦД збільшував кількість TLR2+- та TLR4+ - адипоцитів та переважно підвищував щільність TLR2+- і TLR4+-рецепторів на їх мембрані. Введенням метформіну діабетичним щурам знижали загальну кількість TLR2+- адипоцитів на 16 % (ЕЦД1) - 22 % (ЕЦД2), TLR4+- адипоцитів на 36 % (ЕЦД1), супроводжувалися зменшенням щільності TLR2+- і TLR4+- рецепторів на поверхні жирових клітин. It is researched the influence of experimental diabetes mellitus on the expression of TLR2 and TLR4 by adipocytes of parapancreatic fibrous in the rats of Wistar line. It is detected that the development of EDM increased the number of TLR2+- and TLR4+- adipocytes and increased the density TLR2+- and TLR4+- receptors on their membran. The introduction of metformin to the diabetic rats reduced the general number of TLR2+- adipocytes in 16 % (EDM1) - 22 % (EDM2), TLR4+- adipocytes in 36 % (EDM1) accompanied by the decrease of the density TLR2+- and TLR4+- receptors of the surface of adipose cells.
The peculiarities of the expression of TLR2 and TLR4 adipocytes of parapancreatic connective tissue of experimental diabetes mellitus
Keywords: експериментальний цукровий діабет; адипоцит; TLR2; TLR4; experimental diabetes mellitus; adipocytes